The Impact of YouTube on Loneliness and Mental Health - Luke Balcombe; Diego De Leo (Informatics, 2023)
There are positives and negatives of using YouTube in terms of loneliness and mental health. YouTube’s streaming content is an amazing resource, however, there may be bias or errors in its recommendation algorithms. Parasocial relationships can also complicate the impact of YouTube use. Intervention may be necessary when problematic and risky content is associated with unhealthy behaviors and negative impacts on mental health. Children and adolescents are particularly vulnerable. Although YouTube might assist in connecting with peers, there are privacy, safety, and quality issues to consider. This paper is an integrative review of the positive and negative impacts of YouTube with the aim to inform the design and development of a technology-based intervention to improve mental health. The impact of YouTube use on loneliness and mental health was explored by synthesizing a purposive selection (n = 32) of the empirical and theoretical literature. Next, we explored human–computer interaction issues and proposed a concept whereby an independent-of-YouTube algorithmic recommendation system steers users toward verified positive mental health content or promotions.